Pengembangan Aplikasi Pengenalan Senjata Tradisional Betawi Menggunakan Teknologi Realitas Tertambah Berbasis Android - Asril Kurniawan; Paramaresthi Windriyani (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to produce an application for the introduction of traditional Betawi weapons using Augmented Reality technology. Augmented Reality to provide information to the general public, especially the people of DKI Jakarta. Augmented Reality Technology, which is a technology where users can see objects in three dimensions (3D). This application can help people who want to find information about some traditional Betawi weapons easily by using only a smart device. The method used in software development uses the Multimedia Development Life Cycle (MDLC). To develop this recognition application, the Unity application is combined with vuforia. The results of this study are the application of traditional Betawi weapon recognition with an android operating system that can detect markers and display five types of traditional Betawi weapons in the form of three-dimensional (3D) objects and contain information from each of these weapons.